Administrative Proceeding: From Institute to Branch of Law - Kochubaev, A. (Bulletin of Yerevan University C: Jurisprudence, 2019)
The article attempts to justify the autonomy of administrative proceedings in the context of branches of law, as well as the need to separate administrative proceedings from administrative law. The article consistently substantiates the thesis that, in the context of the subject and method of regulation, administrative law and legal proceedings are at opposite poles and should be separated from this point of view․
Keywords: branch of law, institutե, administrative law, administrative proceedings, object of legal regulation, method